Factors of Innovation Capability That Influence Employee Performance in Public Sector - Martin, Vievianne; Munir, Rosintansafinas; Ma’amor, Hairunnisa (Information Management and Business Review, 2024)
The purpose of this study is to investigate the factors of innovation capability that influence employee performance in the public sector. Most employees lacked knowledge regarding factors of innovation capability that can guide them to innovate when doing tasks. Weak supportive leadership, unwillingness to share knowledge, difficulties to express creativity, and technological barriers prevent them from innovating and performing well in their workplace. A convenience sampling technique was used and a total of 122 public-federal employees participated in this study. This study was conducted on lower to middle management personnel who currently serve as public employees in any federal agencies in the vicinity of Kota Samarahan, Sarawak, Malaysia. The SPSS was applied in assessing the model. The results indicated that significant influence of supportive leadership, knowledge sharing, creativity and technology capability on employee performance in the public sector. This study will serve as a guideline for management to design new strategies in ensuring its employees perform well, the organization would have a good employee performance rate which literally influences the organization’s performance too, and the ideation of policy makers regarding innovative performance among employees can be supported. It was hoped that this study would use other different factors of innovation capability that would influence employee performance with different organizational types or different levels of management for future study.